Pricing by the Firm Under Regulatory Threat - Glazer, A.; McMillan, H. (Quarterly Journal of Economics, 1992)
Amihai Glazer, Henry McMillan; Pricing by the Firm Under Regulatory Threat*, The Quarterly Journal of Economics, Volume 107, Issue 3, 1 August 1992, Pages 1089–